2018
DOI: 10.1016/j.atmosenv.2018.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Modeling dispersion of emissions from depressed roadways

Abstract: This paper presents an analysis of data from a wind tunnel (Heist et al., 2009) conducted to study dispersion of emissions from three depressed roadway configurations; a 6 m deep depressed roadway with vertical sidewalls, a 6 m deep depressed roadway with 30°sloping sidewalls, and a 9 m deep depressed roadway with vertical sidewalls. The width of the road at the bottom of the depression is 36 m for all cases. All these configurations induce complex flow fields, increase turbulence levels, and decrease surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Indeed, several authors have investigated the efficiency of noise barriers in reducing atmospheric pollutant concentrations behind the barriers using in-field (Baldauf et al, 2008(Baldauf et al, , 2016Finn et al, 2010;Hagler et al, 2012;Lee et al, 2018;Ning et al, 2010), wind tunnel (Heist et al, 2009) measurements and numerical models (Bowker et al, 2007;Hagler et al, 2011;Schulte et al, 2014). Some authors have studied the effects of barrier heights and distances on pollution reduction (Amini et al, 2018;Gong and Wang, 2018). Other authors have studied the effects of barrier shapes and locations on improving the reduction of atmospheric pollutants (Brechler and Fuka, 2014; 3/25 Enayati Ahangar et al, 2017;Wang and Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several authors have investigated the efficiency of noise barriers in reducing atmospheric pollutant concentrations behind the barriers using in-field (Baldauf et al, 2008(Baldauf et al, , 2016Finn et al, 2010;Hagler et al, 2012;Lee et al, 2018;Ning et al, 2010), wind tunnel (Heist et al, 2009) measurements and numerical models (Bowker et al, 2007;Hagler et al, 2011;Schulte et al, 2014). Some authors have studied the effects of barrier heights and distances on pollution reduction (Amini et al, 2018;Gong and Wang, 2018). Other authors have studied the effects of barrier shapes and locations on improving the reduction of atmospheric pollutants (Brechler and Fuka, 2014; 3/25 Enayati Ahangar et al, 2017;Wang and Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Noise barriers were originally designed to reduce moving vehicles' noise effects on roadside neighborhood. Studies have suggested that roadside barriers have positive effects on the reduction of downwind pollutant concentration [4][5][6][7][8][9][10][11][12][13][14]. The level of benefits can be influenced by many factors, such as roadway configuration, local meteorology, barrier height, or barrier edge design.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Lee et al studied the combination of noise barrier and roadside vegetation effects on air pollution dispersion under various wind conditions, based on a field study in 2017 [12]. In 2018, Amini et al studied effects of different roadway configurations on near-road contaminant dispersion [13]. Generally, a noise barrier will carry the same length as the length of a roadway.…”
Section: Introductionmentioning
confidence: 99%